In Vitro Propagation of Bambusa balcooa as Alternative Material of Wood - Siti Nurhayani; Rita Megia; Ragapadmi Purnamaningsih (Biosaintifika: Journal of Biology & Biology Education)
A diversion of raw material from wood to bamboo is necessary. In vitro culture of bamboo can be used to provide a high number of seedling. The aim of this study was to increase the multiplication of a high quality Bambusa balcooa as a wood alternative material. Part of plants used was the sterile axillary shoot. The explants were planted on MS0 medium for 2 weeks and later on multiplication medium MS+0.3 mg/l BAP + 0.3mg/l TDZ. The shoots obtained were fragmented into clusters (3-5 shoots) used for the next multiplication stage using five different medium formulas: (1) MS0; MS containing: (2) 0.1 mg/l BAP, (3) 0.3 mg/l BAP, (4) 0.1 mg/l BAP + 0.1 mg/l TDZ and (5) 0.3 mg/l BAP + 0.1 mg/l TDZ. The results showed that MS medium containing 0.1 mg/l BAP + 0.1mg/l TDZ was the best medium for B. balcooa propagation. The shoots produced from aforementioned medium had a better quality compared to the other medium. Forty days after planting, the average number of shoots in this medium was 14.25. MS medium containing 0.3 mg/l BAP + 0.1 mg/l TDZ produced the highest number of shoot but in lower quality. Rooting medium containing 10 mg/l IBA + 5 mg/l NAA produced 9-16 root in 8 weeks. Vermicompost was more prevalent for the acclimatization of B. balcooa compared to compost. The use of B.balcooa resulted in in vitro propagation as a substitute alternative for wood is expected to save the environment from illegal logging.